Morality: The matters of artificial insemination: Luân Lý: Vấn đề thụ tinh nhân tạo - Phạm, Đông Hòa (Khoa Học Công Giáo và Đời Sống, 2022)
Infertility is one of the big problems in today's world. This is also one of the causes of division and broken families. As Christians, we are called to live and bear witness to the Gospel in today's life. At the same time, know how to accompany families in this situation so that they can find the best means (approved by the Church) that can bring joy and peace to those families.